Pengaruh Model Pembelajaran Everyone is a Teacher Here (ETH) Terhadap Kemampuan Berpikir Kritis Siswadalam Pembelajaran PAI di SMK Negeri Winongan - Muhammad Nabil Hisyam; M. Ma’ruf; Siti Halimah (Tarbiyatuna Kajian Pendidikan Islam, 2025)
Critical thinking skills are a topic that involves the use of the everyone is a teacher here (ETH) learning model in PAI (Religious Education) learning at SMK Negeri Winongan. This study aims to determine the effect of the everyone is a teacher (ETH) learning model on students critical thinking skills in PAI learning at SMK Negeri Winongan. This research employs a quantitative research type with an ex-post facto and descriptive approach. The results show that there is an effect of the everyone is a teacher here (ETH) learning model on students critical thinking skills, as seen from the T test results, namely,  (18.578 ? 1.664), thus  (there is an effect) is accepted. In the simple linear regression test, a constant value of +2,194 (+21,94%) and a regression coefficient of X of 0,449 (44,9%) were obtained, indicating a positive influence of the everyone is a teacher here (ETH) learning model on students critical thinking skills.